Dust Emissions from Landfill Deposition: A Case Study in Malmberget Mine,Sweden - Jia, Qi; Huang, Yi; Al-Ansari, Nadhir; Knutsson, Sven (Luleå tekniska universitet, Geoteknologi, 2013)
A great amount of industrial wastes are produced in Sweden every year. In 2008 there were 97.9 million tons of wasted generated, among which 93 million tons industrial waste were produced. 64.1% of industrial wastes were deposited in the landfill sites. Dust generation is one of the most important problems associated with industrial waste and landfills. The particulate dust emissions come from the industrial waste may contain heavy metal and produce environmental problems and potential health risks. Active and passive samplers, deposition pans are common equipment to collect dust samples. Real-time monitors use laser diffraction to recording continuous dust concentration. Dust emission from Malmberget mine in Sweden was analyzed as a case study. Dust was collected by NILU deposit gauge from 26 stations. Generally speaking the amount of dust fallout was decreasing with time because of implemented dust control methods. During the period August 2009 to August 2010, among all the measuring stations through the year, the maximum and the minimum value were 1284 g/100m2/30d and 9 g/100m2/30d. Two sources of dust generation were identified. The first was located close to the open pit, and the second near the current mining industrial center. The dust generation due to road construction was calculated. Validerad; 2013; 20130717 (nadhir)